Experimental and numerical analysis of the consolidation process for additive manufactured continuous carbon fiber-reinforced polyamide 12 composites - Zhilyaev, Igor; Grieder, Stefan; Küng, Marco; Brauner, Christian; Akermann, Michael; Bosshard, Jonas; Inderkum, Petra; Francisco, João; Eichenhofer, Martin (Frontiers in Materials, 2022)
Substitution of conventional metal structures with fiber-reinforced polymers is possible because of their sustainable performance. One of the primary disadvantages of these composite materials is their high cost due to labor-intensive manufacturing. Because the fiber path can be steered directly along the load path, structures can be manufactured in a near-net shape, and a high degree of reproducibility with low scrap rates can be achieved. Additive manufacturing of these composite structures could enable cost efficiency with a high degree of complexity. However, the high degree of porosity and high void content between the printed fiber filaments results in unacceptable structural performance. Following the printing process, a post-consolidation process (additive fusion) can be performed to improve the mechanical performance of the part and use fiber-reinforced polymers for load-bearing applications. Numerical simulation of the consolidation process enables the production of these complex parts without expensive prototyping iterations. Because of the rapid and local changes in material stiffness, the simulation of the consolidation process is combined with a set of numerical model convergence problems. An advanced finite-element numerical model for simulating the consolidation process of additive manufactured continuous fiber composite parts is presented in this paper. The additive fusion step simulation allows for the evaluation of process-induced deformations, final engineering constants, and porosity. The simulation workflow is demonstrated and validated using experimental data from the manufacturing process of a typical aerospace part, specifically a helicopter hinge element.